Molecular mechanisms of ROS production and oxidative stress in diabetes - Newsholme, Philip; Cruzat, Vinicius Fernandes; Keane, Kevin Noel; Carlessi, Rodrigo; de Bittencourt, Jr, Paulo Ivo Homem (Biochemical journal, 2016)
Oxidative stress and chronic inflammation are known to be associated with the development of metabolic diseases, including diabetes. Oxidative stress, an imbalance between oxidative and antioxidative systems of cells and tissues, is a result of over production of oxidative-free radicals and associated reactive oxygen species (ROS). One outcome of excessive levels of ROS is the modification of the structure and function of cellular proteins and lipids, leading to cellular dysfunction including impaired energy metabolism, altered cell signalling and cell cycle control, impaired cell transport mechanisms and overall dysfunctional biological activity, immune activation and inflammation. Nutritional stress, such as that caused by excess high-fat and/or carbohydrate diets, promotes oxidative stress as evident by increased lipid peroxidation products, protein carbonylation and decreased antioxidant status. In obesity, chronic oxidative stress and associated inflammation are the underlying factors that lead to the development of pathologies such as insulin resistance, dysregulated pathways of metabolism, diabetes and cardiovascular disease through impaired signalling and metabolism resulting in dysfunction to insulin secretion, insulin action and immune responses. However, exercise may counter excessive levels of oxidative stress and thus improve metabolic and inflammatory outcomes. In the present article, we review the cellular and molecular origins and significance of ROS production, the molecular targets and responses describing how oxidative stress affects cell function including mechanisms of insulin secretion and action, from the point of view of possible application of novel diabetic therapies based on redox regulation.